Pengaruh Media Pembelajaran Crossword Puzzle dalam Meningkatkan Minat Belajar Siswa pada Mata Pelajaran IPS Kelas Lima di SDN 53 Sawerigading Palopo - Tahir, Ririn; Baderiah; Bungawati (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to determine the effect of using crossword puzzle learning media on students' learning interest and the improvement of students' learning interest in the Social Science subject for Grade V at SDN 53 Sawerigading Palopo. This study uses a quantitative approach with a quasi-experimental design through a nonequivalent control group design. The research subjects consist of two classes, namely the experimental class and the control class. Data collection techniques were carried out through student learning interest questionnaires. Data analysis used descriptive analysis, normality test, homogeneity test, Independent Sample T-Test, and Paired Sample T-Test with the assistance of IBM SPSS version 25. The research results show that the average learning interest of students in the experimental class increased from 51.42 in the pretest to 57.58 in the posttest, while in the control class it increased from 49.27 to 52.82. The results of the Independent Sample T-Test showed a significance value of 0.000 < 0.05 with a calculated t-value of 5.275, indicating a significant difference between the experimental class and the control class. In addition, the results of the Paired Sample T-Test showed a significance value of 0.000 < 0.05 with a calculated t-value of -7.313, indicating a significant increase in learning interest after using the crossword puzzle media. Thus, the use of crossword puzzle learning media has a significant effect and is able to increase student learning interest in the Grade V IPAS subjects at SDN 53 Sawerigading Palopo.